2009
DOI: 10.3944/aott.2009.021
|View full text |Cite
|
Sign up to set email alerts
|

Functional results of the parallel-plate technique for complex distal humerus fractures

Abstract: Functional results are satisfactory in distal humerus fractures treated with stable osteosynthesis and parallel-plate technique that allow early active motion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
3
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 18 publications
4
26
3
7
Order By: Relevance
“…Similar results have been recently reported with the use of precontoured LCP by other authors [17][18] . In our study, average time interval between admission of patients and surgery was 7.8 days (Ranged 4 -13 days) which is slightly higher than in the studies reported by Atalar et al (2009) 6 days [19] . The average time to union in our study was 13.8 weeks (Ranged 12-18 weeks) which was slightly greater than as reported by Pankaj et al (2007) 12.8 weeks [20] but was less than in study reported by Georgiades et al (2010) 16 weeks [9] .…”
Section: Discussioncontrasting
confidence: 52%
“…Similar results have been recently reported with the use of precontoured LCP by other authors [17][18] . In our study, average time interval between admission of patients and surgery was 7.8 days (Ranged 4 -13 days) which is slightly higher than in the studies reported by Atalar et al (2009) 6 days [19] . The average time to union in our study was 13.8 weeks (Ranged 12-18 weeks) which was slightly greater than as reported by Pankaj et al (2007) 12.8 weeks [20] but was less than in study reported by Georgiades et al (2010) 16 weeks [9] .…”
Section: Discussioncontrasting
confidence: 52%
“…[13] On the other hand, delayed union, nonunion, necessity of implant use to repair osteotomy, and prominent hardware that leads to a second surgery are among the disadvantages. [7][8][9]14,15,23,24] Furthermore, nerve supplies of the anconeus muscle might be damaged, as this muscle participates in the dynamic stabilization of the elbow joint, this may cause elbow instability. [23] Wilkinson et al [13] have compared the triceps split, TRAP, and olecranon osteotomy techniques in a cadaveric study.…”
Section: Discussionmentioning
confidence: 99%
“…[23,24] Perfect exposure of the fracture is a key factor that allows restoration of articular surfaces. Thus, many approaches were defined, such as olecranon osteotomy, triceps reflecting, triceps splitting, and TRAP approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Parallel plating of comminuted distal humerus fractures was reported by few authors. Atalar AC et al [8] evaluated 21 such cases. All fractures were united and the average MEPS score was 86 points.…”
Section: Discussionmentioning
confidence: 99%